Sukhāce sobatī - Caughule, Viśvanātha Śaṅkara (Anaghā Prakāśana, 2016)
Reminiscences of the author about his friends and associates
In Marathi
Keywords: Autobiografie; Caughule; Viśvanātha Śaṅkara; Authors; Marathi